Responses of Growth and Grain Yield of IR50404 Rice to Temperature Stress - Le Huu Phuoc; Irfan Suliansyah; Feri Arlius; Irawati Chaniago; Nguyen Thi Thanh Xuan; Pham Van Quan (International Journal of Agricultural Sciences, 2022)
Climate changes, rising warmth, drought, and CO2, are now seriously influencing agriculture. In this study, four separate greenhouses (labeled GH1, GH2, GH3, and GH4) were built with plastic roofs and walls, except GH1, which had three walls with mesh to evaluate the impact of temperature stress on growth, biomass, and yield of rice variety IR50404 under different temperature regimes. The control treatment group was grown ambient, next to these greenhouses. GH1, GH2, GH3, and GH4’s temperatures were from 0.9 oC to 3.1 oC higher than the ambient (as control). Carbon dioxide concentrations in GH2, GH3, and GH4 were recorded higher than the ambient, from 34.1 ppm to 48.2 ppm. Total vegetative dry matter was reduced from 15.9% to 20.5%, while grain yield declined from 20.8% to 24.6% when the mean temperature increased from 2.9 oC to 3.1 oC. High temperature or a combination of high-temperature stress with elevated CO2 concentration reduced the grain yield and total vegetative dry matter.